The Role of Impulse Oscillometry in Evaluating Disease Severity and Predicting the Airway Reversibility in Patients With Bronchiectasis - Tan, Cuiyan; Ma, Donghai; Wang, Kongqiu; Tu, Changli; Chen, Meizhu; Zheng, Xiaobin; Liang, Yingjian; Huang, Yiying; Wang, Zhenguo; Wu, Jian; Huang, Jin; Liu, Jing (Frontiers in Medicine, 2022)
Background Impulse oscillometry (IOS) can be used to evaluate airway impedance in patients with obstructive airway diseases. Previous studies have demonstrated that IOS parameters differ between patients with bronchiectasis and healthy controls. This study aims to explore the usefulness of IOS in assessing disease severity and airway reversibility in patients with bronchiectasis. Method Seventy-four patients with non-cystic fibrosis bronchiectasis who visited our Respiratory Medicine outpatient clinic were consecutively recruited. Spirometry, plethysmography and IOS tests were performed. Patients were stratified into mild, moderate and severe disease according to Reiff, Bhalla, BSI, FACED, and BRICS scores. Airway reversibility was measured by bronchodilation test (BDT) and the result was classified as positive or negative. ROC curves of IOS parameters were used to assess the usefulness of IOS parameters in predicting airway reversibility. Correlations between the IOS, spirometric lung function and bronchiectasis severity parameters were analysed. Results Many IOS parameters, such as airway resistance at 5Hz (R5), small airways resistance (R5–R20), total airway reactance (X5), resonance frequency (Fres), total airway impedance at 5Hz (Z5), and peripheral resistance (Rp) increased in patients with bronchiectasis who presented a moderate to severe severity as categorised by the FACED, BSI and Reiff scores. Large airway resistance (R20) and central resistance (Rc) were not significantly different among groups with different bronchiectasis severity. The difference between R5 and R20 (R5-R20) showed 81.0% sensitivity, and 69.8%specificity in predicting the airway reversibility in bronchiectasis with AUC of 0.794 (95%CI, 0.672-0.915). Conclusion IOS measurements are useful indicators of bronchiectasis severity and may be useful for predicting the airway reversibility.